Ethical public typology: How does moral foundation theory and anticorporatism predict changes in public perceptions during a crisis? - Hong, Seoyeon; Shim, Kyu Jin (John Wiley and Sons Inc, 2023)
This study proposes a new public typology utilising moral foundation theory and anticorporatism. The current paper conceptualised four ethical types of public (e.g.,moralists,antagonists,optimists,and pragmatists) and conducted an online survey using a national sample (N = 1124) to test the applicability of the new typology. Our results suggest that different types of publics react differently in attributing crisis responsibility,expressing their emotional responses,and showing boycott intentions in evaluating a corporate crisis. © 2022 The Authors. Journal of Contingencies and Crisis Management published by John Wiley & Sons Ltd.
Keywords: Ethics; Perception; Segmentation; Typology; Anticorporatism; Boycott; Crisis attribution; Emotions; Ethical consumerism; Moral foundation theory; Public segmentation; 61 Psicología::6114 Psicología social; ODS 3 - Salud y bienestar; ODS 16 - Paz, justicia e instituciones sólidas